A qualitative enhancement to quantitative social network analysis. Issue 4 (8th August 2021) - Cooray, Shavindrie
Abstract: The literature on social media analytics typically focuses on the social processes within the social media group that is being studied. On the other hand, the subjective views of the social media analysts have received less attention. Here, we demonstrate that the subjectivity of the analyst can have a bearing on both qualitative and quantitative social network analytics. We provide a methodology to analyze the analysts' subjective frames of reference and their impact on the way they interpret the social group under study and also the social context within their organization that prompted the inquiry in the first place. We offer a methodology for analyzing the types of resources, characteristics, and knowledge held by key influencers in a social media group, and then use the findings to better understand the frames of reference of its members at large. We propose that social media analytics should be carried out by groups of analysts who discuss their individual viewpoints and bring about a "fusion of horizons, " in contrast to the prevalent practice of analysts conducting the analysis alone. We test our methodology with a study of #Blogchat, the largest live chat group on Twitter.